Changepoints of annual flood-layer from sediment core POS362-2_33 - Blanchet, Cécile L; Ramisch, Arne; Tjallingii, Rik; Ionita, Monica; Laruelle, Louison; Meike, Bagge; Klemann, Volker; Brauer, Achim (PANGAEA, 2024)
The dataset provides information about changepoints identified in the sediment accumulation rate profile of marine core POS362_2_33. The study site is located on the Nile deep-sea fan and the core was collected in 2008. Using annual layer thickness determination (see doi:10.1594/PANGAEA.967743), sediment accumulation rates were calculated and eight changepoints were detected. We report here the depth and age of each changepoints and the number and average thickness of flood-layers between each changepoint. Further details can be found in the related
Keywords: flood frequency; Green Sahara; Nile River; Varve